Training and fatty acid metabolism - Kiens, B. (Advances in Experimental Medicine and Biology, 1998)
Older studies in humans seem to suggest a correlation between plasma long chain fatty acid (LCFA) turnover and oxidation on the one hand and plasma LCFA concentration on the other hand during submaximal exercise. However, recent studies in man, in which higher concentrations of plasma LCFA have been reached during prolonged submaximal exercise, have revealed a levelling off in net uptake in spite of increasing plasma LCFA concentrations. Furthermore, this relationship between plasma LCFA concentration and plasma LCFA uptake and oxidation was altered by endurance training such that levelling off was not apparent in the trained state. These recent findings in man give support to the notion from other cell types that transport of fatty acids from the vascular compartment to the cytosolic space in the muscle cell is not only due to simple diffusion, but is predominantly carrier-mediated. During prolonged submaximal knee-extension exercise it has been demonstrated that the total oxidation of LCFA was approximately 60% higher in trained compared to nontrained subjects. The training-induced adaptations responsible for this increased utilization of plasma fatty acids by the muscle could be located at several steps from the mobilization of fatty acids to skeletal muscle metabolism in the mitochondria. To what extent triacylglycerol located in the muscle cell contribute to the overall lipid utilisation during exercise is still not clear. However, due to underestimation of the contribution of plasma LCFA and fatty acids liberated from the circulating VLDL-triacylglycerols to the overall fatty acid oxidation during exercise there is increasing understanding that muscle triacylglycerol contributes to a lesser extent as fuel during exercise in man than mostly stated.